EFL Learners’ English Engagement in LinkedIn-Based Professional Digital Practices: Exploring Career-Oriented Motivation - Mukhollafah, Wildani; Ekowijayanto, Mochlis (IJORER : International Journal of Recent Educational Research, 2026)
Objective: Many students today consider English as an essential requirement for entering the workforce, especially because professional activities are increasingly conducted in the digital realm. Platforms like LinkedIn are more frequently exposing students to the use of English in real professional contexts, ranging from preparing for the job application process to the demands of professional communication in English. This situation encourages students to pay more attention to learning English through various digital media outside the classroom. The purpose of this research is to examine the relationship between career-oriented motivation and EFL learners’ engagement in learning English on LinkedIn as a professional digital space. Method: This research uses a mixed-method approach with a sequential explanatory design and involves 28 advanced students from English education programs at two universities in Probolinggo. Data were collected using two main instruments: questionnaires and daily reflection journals. Quantitative data were analyzed using descriptive statistics and Chi-square tests, while qualitative data were analyzed thematically. Findings: The study’s findings indicate that LinkedIn provides a digital professional space that familiarizes students with English-language communication practices in the workplace. This exposure is linked to students’ growing awareness that English is a crucial component of professional development. Although motivation levels did not show a significant correlation with the frequency of LinkedIn use, students with stronger professional motivation tended to practice professional English communication more actively in the digital space. Novelty: This study expands research on informal digital English learning (IDLE) by demonstrating that professional digital platforms such as LinkedIn help shape EFL learners’ perceptions of the importance of English in the workplace and encourage them to engage more actively in English learning through various digital practices outside the formal education setting.